Nonlinear Control Of Unified Power Flow Controller (UPFC) For Power System Stabilization - Hannon, Naeem (2009)
The Study of Unified Power Flow Controller (a FACTS device) in improving transient stability and providing independent control of power flow in the transmission lines of a power system has been undertaken in this research. The various control strategies for the UPFC comprising series and shunt voltage source converters have been presented in several chapters of this thesis.